Implementation of Islamic Higher Education Development Management in Indonesia - Aliyah, Hikmatul; Anif, Muhammad; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Since the inauguration of Islamic Higher Education (STI) in Jakarta in July 1945, before Indonesia gained independence, the growth of Islamic tertiary institutions has been ongoing in Indonesia. Since then, Islamic tertiary institutions have started to flourish and change. After STI’s creation, it became UII (Indonesian Islamic University). Following advancements at the UII faculty of religion, PTAIN (State Islamic Religious College), IAIN, and STAIN were nationalized. Additionally, private Islamic higher education took the shape of universities, institutions, or high schools. The three primary pillars of the new higher education paradigm are as follows: First, increased independence (greater autonomy) in management or autonomy. Second, increased responsibility or accountability, not just in terms of financial resources more responsibly, as well as in scientific research, educational materials, and on-going initiatives. Third, improved quality assurance through continuous internal assessments and National Accreditation Board external assessments (BAN).